Haldane phase in one-dimensional topological Kondo insulators - Mezio, Alejandro (2015)
We investigate the ground-state properties of a recently proposed model for a topological Kondo insulator in one dimension (i.e., the p-wave Kondo-Heisenberg lattice model) by means of the density-matrix renormalization-group method. The nonstandard Kondo interaction in this model is different from the usual (i.e., local) Kondo interaction in that the localized spins couple to the "p-wave" spin density of conduction electrons, inducing a topologically nontrivial insulating ground state. Based on the analysis of the charge- and spin-excitation gaps, the string order parameter, and the spin profile in the ground state, we show that, at half filling and low energies, the system is in the Haldane phase and hosts topologically protected spin-1/2 end states. Beyond its intrinsic interest as a useful "toy model" to understand the effects of strong correlations on topological insulators, we show that the p-wave Kondo-Heisenberg model could be experimentally implemented in p-band optical lattices loaded with ultracold Fermi gases.